Use of polyethylene glycol precipitation and ultracentrifugation to enhance the sensitivity of hepatitis B virus DNA detection - Fu, Michael X.; Larralde, Osmany; Mayne, Richard; Kean, Kai; Reid, Kaitlin; Andersson, Monique; Golubchik, Tanya; McKeating, Jane A.; Jarvis, Lisa; Irving, William L.; Simmonds, Peter; Harvala, Heli (Elsevier BV, 2025)
Background: Sensitive molecular detection of hepatitis B virus (HBV) DNA is crucial for diagnosing and managing occult hepatitis. To improve the sensitivity of HBV DNA detection, we compared the effectiveness of polyethylene glycol (PEG) precipitation and ultracentrifugation to concentrate DNA prior to extraction.
Methods: Twenty-three HBV DNA-positive samples with low viral loads were compared between the extraction of standard (0.2 mL) and larger volumes (5 mL) of plasma, through PEG precipitation of 10 mL and 20 mL of plasma, and ultracentrifugation from 35 mL of plasma. The effectiveness of the methods for HBV DNA detection was assayed by quantitative PCR. For genetic characterisation, Sanger sequencing of amplicons and targeted Illumina sequencing were used. Costs, sample capacities, and turnaround times were compared.
Results: DNA was detected in a greater number of samples using PEG and ultracentrifugation (detecting up to all 23 samples) compared to more standard extraction methods (detecting at least 18 samples). Efficiencies of recovery of HBV DNA from samples were comparable in all concentration methods. HBV and other DNA viruses, such as human herpesviruses and anelloviruses, were detected in samples and at higher read counts with PEG concentration than without. The availability, cost, relative simplicity, and throughput of PEG precipitation conferred further advantages to ultracentrifugation.
Conclusions: PEG precipitation from large volumes of plasma is a practical and economical alternative to ultracentrifugation and could be a similarly effective concentration method for low viral load samples in blood donation and clinical virology laboratories.